Zine art and deaf identity in Indonesia: a practice-led phenomenological exploration of inclusive visual expression - Imam, Chairol; Dawami, Angga Kusuma; Marwanto, Aris Budi (Pascasarjana Institut Seni Indonesia Surakarta, 2025)
Deaf individuals primarily rely on visual modes of communication such as sign language, which also function as powerful expressions of cultural identity. Despite this, their representation within the arts remains limited, particularly in Indonesia, where access and inclusion are still developing. This study explores how visual art, specifically zine-making, can serve as an inclusive and culturally grounded creative space for the Deaf community, emphasizing the interaction between Deaf identity, sign language, and visual expression. Rooted in a constructivist epistemology, this research is grounded in the belief that knowledge is actively constructed through interaction, experience, and meaning-making. To support this philosophical stance, the study employs three interrelated methodologies: Practice-Led Research to guide the artistic process and creative exploration; Aesthetic Phenomenology to examine the lived and embodied experiences of visual creation and reception; and Actor-Network Theory (ANT) to analyze the relational dynamics among human and non-human actors involved in the zine-making process. Through collaborative artistic engagement with Deaf individuals and reflective documentation of their interactions, the study reveals that zines function not only as artistic outcomes but also as inclusive communication tools that bridge the Deaf and hearing worlds. Visual elements inspired by BISINDO (Indonesian Sign Language) operate as symbolic markers of Deaf identity, while the integration of grapyak, a Javanese cultural value emphasizing hospitality, supports the formation of inclusive aesthetics rooted in local traditions. This research contributes to the field of disability arts by demonstrating how zine-making can serve as a site of cultural dialogue, visual empowerment, and artistic inclusion. It also provides a model for integrating local cultural values into inclusive visual practices.